Reengineering the training function : how to align training with the new corporate agenda - Shandler, Donald (St. Lucie P. Boca RatonUS, 1996)
Identifies new corporate realities that affirm the urgent need for more effective training and performance interventions. Argues that reengineering training must replace the traditional training function. Presents it as a win-win strategy that benefits both the organization and training. Identifies and discusses globalization of business, and new technologies as special challenges for reengineering.